The role of the glucocorticoid receptor gene (NR3C1) for the processing of aversive stimuli. (June 2016) - Schneider, Katja Kerstin; Frings, Christian; Meyer, Jobst; Schote, Andrea B.
Highlights: We studied effects of functional polymorphisms of the GR-encoding gene ( NR3C1 ). The NR3C1 -CTGGACA haplotype influenced the processing of affective stimuli. There were no effects on the processing of neutral stimuli. This result stresses the importance of the GR for basal emotional processing. Abstract: The glucocorticoid receptor (GR) is a crucial component of the hypothalamus–pituitary–adrenal (HPA) axis and as such a part of the stress response system. An impairment of the GR not only alters the level of glucocorticoids, but also modulates cognitive functions and the processing of emotional stimuli. We tested the effects of functional polymorphisms of the GR-encoding gene ( NR3C1 ) on the processing of emotional stimuli on a basal level. In a sample of n  = 182 participants, we found a haplotype ( NR3C1 -CTGGACA) to modulate the performance in an emotional reaction time task. Compared to non-carriers, participants who carried the haplotype were quicker to react after aversive stimuli had been presented. In contrast, the presence of the haplotype had no effect on the processing of neutral stimuli. We conclude that properties of the glucocorticoid receptor contribute to the processing of emotional stimuli and influence the intensity of their processing even in the absence of acute stressors.